The Impact of Consumer Experience on Women’s Clothing Brand Equity and Influencer Partnership on Consumer Behaviour - Esa Prasanthi Candrika; Ida Nyoman Basmantra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Digital transformation has reshaped the global fashion industry through the rise of e-commerce, social media marketing, and strategic influencer partnerships. In Denpasar City, women entrepreneurs leverage digital marketing to overcome social and gender-related challenges while enhancing competitiveness and customer loyalty through personalized consumer experiences. This study examines the effects of consumer experience, brand image, brand equity, and influencer partnership on consumer behaviour among women who have purchased women’s clothing products. A total of 102 female respondents participated in this quantitative study. Data were collected via questionnaires and analyzed using SmartPLS 3, including measurement model testing (outer model), structural model evaluation (inner model), and hypothesis testing. The results show that consumer experience and brand image positively and significantly influence brand equity. Both consumer experience and brand image also positively affect consumer behaviour, while brand equity further strengthens consumer behaviour. Additionally, influencer partnership moderates the relationship between brand equity and consumer behaviour, and brand equity mediates the effects of consumer experience and brand image on consumer behaviour. These findings suggest that women entrepreneurs in the women’s fashion industry should focus on maintaining consistent visual communication, improving social media content, and delivering enjoyable offline and online shopping experiences to enhance brand equity and consumer behaviour. Future research could explore additional variables and broader contexts to gain a more comprehensive understanding of the factors shaping consumer behaviour in the women’s fashion sector.